Sustainability Reporting for Sustainable Development: A Bibliometric Analysis - Pedrazzi, Ana Luiza; Queiroz, Juliana Molina (Technical and Scientific Journal Green Cities, 2025)
ABSTRACTObjective – This study aims to present a bibliometric analysis of the literature on Sustainability Reports which can collaborate in the pursuit of the Sustainable Development Goals (SDGs).Methodology – Published works are quantitatively analyzed regarding the main articles, authors and magazines involved in the topic around the world. In that sense, issues such as the relevance of articles, authors and journals are analyzed based on the number of publications and citations. Furthermore, the main words cited in these articles that make up the sample were analyzed. Originality/relevance – This study presents general information that can be useful to facilitate the understanding of the state of the art of science on Sustainability Reports, since according to Berrone (2023), research can contribute to the implementation of Sustainable Development, and it is necessary that we analyse the literature aiming to develop it further.Results – Relevant metrics are presented to analyze the evolution of the topic in the literature. The bibliometrics includes the analysis of 4402 articles published between 1990 and 2024. The results present five analyses: the ten most relevant journals according to the number of publications; the cumulative number of publications over the years in each of the ten magazines with the most publications; the most relevant articles according to the number of citations; the number of publications by countries; and the word cloud with the main words cited in the articles that make up the sample. Theoretical/methodological contributions – It is noteworthy that this study presents general information that can be useful to facilitate the understanding of the state of the art of science on Sustainability Reports. Among the main results, they suggest an international trend towards the idea of ​​Sustainable Development, which is more prominent in articles dealing with Sustainability Reports.Social and environmental – This study shows that there appears to be a trend in publications on Sustainability Reports that relate them to the idea of ​​Sustainable Development, suggesting that the two issues are intrinsically related. In other words, it is possible that Sustainability Reports can actually collaborate with Sustainable Development through the use of reports as an information tool about the social and environmental contributions made by entities.
Keywords: Sustainability report; Bibliometrics; Bibliometric Analysis; Sustainable Development